Practical work, research, and education facilitating interprofessional work (IPW) -Considering examples of efforts in Nagasaki - Teshima, Mugen (Japanese Journal of Community Medicine and Pharmaceutical Sciences, 2024)
Clinics, pharmacies, and visiting nursing stations involved in home care support require human resource development and education that facilitate the performance of interprofessional work (IPW) in addition to medical information sharing systems and human networks between hospital and community medical care staff. It was confirmed that promoting community-participatory interprofessional education (IPE) deepens the understanding of other professions. IPE is the foundation of human network-based training/education and medical information collaboration in IPW. In this study, I will introduce various IPE and IPW initiatives in Nagasaki, including the author’s own activities.